Measurement of sediment particle size distribution and shape using dynamic imaging analysis. Issue 1 (1st September 2022) - Arora, N; Kumar, A; Singal, S K
Abstract: Hydropower plants operating in fragile mountainous regions face severe sediment erosion of hydraulic turbines, resulting in decreased efficiency, frequent power interruptions, and downtime for maintenance. The sediment size and shape are detrimental to the hydraulic turbines and influence sediment erosion. Sediment management is a crucial aspect of tackling sediment erosion in hydraulic turbines. The traditional method of measuring particle size and shape is time-consuming, labour-intensive, and usually requires statistical analysis. The present study applies the recent technique of dynamic imaging analysis to determine the particle size distribution and shape of sediment. Five different silt-sand mixtures have been used to check the ability of dynamic imaging analysis. Further, the repeatability and reliability of the results were checked by carrying out five repeated measurements of each sample under the same condition in a short period of time. This study will help the researchers and sedimentologists to adopt the dynamic imaging analysis technique for measuring particle size and shape and help the instrument developer in designing a better future version of the instrument.